Pemenuhan Hak Narapidana Anak Sebagai Upaya Perlindungan di Lembaga Pemasyarakatan Kelas II B Kota Sorong - Tarwiyah, Sintia; Tuasikal, Hadi; Sriyati, Sriyati (LPPM Universitas Ekasakti Padang, 2024)
This study aims to examine how efforts to fulfill the rights of child prisoners and the implementation of child prisoner development in correctional institutions class II B Sorong City. The research used through empirical juridical legal research methods through a qualitative approach with material analysis using qualitative descriptive analysis techniques. The results of this study indicate that (1) Efforts to protect the rights of child prisoners in the Class II B Correctional Institution of Sorong City based on Law Number 22 of 2022 concerning Corrections. Its implementation runs in accordance with existing regulations. However, in granting these rights, it is necessary to pay attention to the development of child prisoners, including the growth and development of children, both physical, mental, and social, so it is not justified if the development and protection of child prisoners are equalized with adult prisoners. According to Lawrence M Friedmann, the success of law enforcement is determined by three elements of the legal system, namely: Legal structure, legal substance, and legal culture. First Legal Substance, in this case there is no new government regulation after Law Number 22 of 2022 concerning Corrections. Second Legal Structure, in this case the overcapacity that occurs in the Correctional Institution class II B Sorong City can affect the performance of the Institution itself so that extra services are needed for prisoners. Third Legal Culture, the existence of prisons that cannot keep up with the number of incoming prisoners, it is necessary to increase awareness of the legal culture of the community so that crime can be minimized and can reduce the number of incoming prisoners. (2) The existence of child prisoners who are still integrated with adult prisoners due to overcapacity needs to be addressed properly because the implementation should be specifically placed in the Child Special Development Institution (LPKA) based on the provisions of Article 47 of Law Number 22 of 2022 concerning Corrections.